Molecular pharmacological studies of CHFI-FXII interaction and FXII function - Kareem Hamad, B. (2016)
Corn Hageman factor inhibitor (CHFI) is a bifunctional serine protease / α-amylase inhibitor protein having 127 residues and a molecular weight of 13.6-kDa. CHFI is selective toward FXIIa without affecting the function of the other coagulation factors. Coagulation FXII is a serine protease recognized to cause kinin generation and blood coagulation, cleaving plasma kallikrein and FXI. Results from FXII-deficient animal models proposed that this protein contributes to stable thrombosis that can cause obstruction of the blood vessels and its subsequent complications such as ischemic stroke. In contrast to other blood coagulation factors, deficiency in FXII is not related with haemorrhage in patients or in animals. These findings propose that specific inhibition of FXII could be an attractive medicine and a new method of anticoagulation to treat or prevent pathological thrombosis that could have a lower risk for bleeding and a safer anticoagulation profile than the currently available anticoagulants. Therefore, the current PhD project aimed at pharmacological investigation into CHFI-FXII interaction and FXII function at molecular level through the following objectives: first, developing an efficient expression and purification system for generating soluble and functional recombinant native type CHFI and establishing an inhibitory activity assay against FXIIa to verify the proper function of the recombinant protein. The second objective was testing the different recombinant variants of CHFI with the desired point mutations guided by a proper prediction study of CHFI-FXII interaction. The third was to investigate into the hypothesis of the tight-binding property of CHFI via different approaches of enzyme inhibition mechanisms and kinetic data analysis. The last objective was to investigate into the function of FXII by examining theeffect of Cys466 and glycosylated peptide remnant from the proline-rich region on the function of the catalytic domain via characterizing the different recombinant variants of the catalytic domain of FXIIa, FXIIc, FXIIac, HISTF-β FXII, and MBP-β-FXIIa. In the current study, an efficient system for soluble expression, single step purification and proper storage of functional, wild type rHIS-GST-CHFI was, for the first time, identified. The fully functional recombinant protein was verified via developing an inhibition test against FXIIa. The established expression, purification and inhibition assays were used as a fundamental guide to both generating and characterizing mutant proteins of interest that were made on the basis of an appropriate docking model of CHFI-FXIIa interaction. For the first time, the current investigation into the question of specificity of CHFI against FXII revealed that the central Arg34 at the very top of the fully exposed region of CHFI inhibition loop play a central role in the inhibition function of CHFI toward FXIIa. In addition, this study identified Trp22 at the N-terminus and Arg43 at the C-terminus of the central inhibition loop as two key interaction residues with FXIIa. It was also observed that, in the preinhibition test, CHFI behaves as a noncompetitive inhibitor. In contrast, it acts as a competitive inhibitor in the acute inhibition test, proposing that CHFI is a competitive inhibitor with slow degree of reversibility due to tightness of binding. Reversibility assay showed that CHFI is an inhibitor with slow degree of dissociation. The tight-binding property of CHFI could be due to a non-active site interaction and or numerous hydrogen bonds between the III key interaction residues and their potential targets on FXIIa.With respect to the investigation into FXII function, It was observed that both Cys340-Cys466 and glycosylated peptide fragment of the proline-rich region have a functional role for the full catalytic activity of FXII protease domain. Cumulatively, the current study identified the key important residues on the exposed surface of CHFI and their potential target residues on the surface of FXIIa that would be highly informative and important factors helping to understand the mechanism of selective and tight binding interaction of CHFI with FXIIa. This project can be considered as an early, necessary approach to design novel, specific and safe anticoagulants for the treatment of thrombosis and its complications.